Relationship of ACTN3 R577X gene to flexibility and range of motion: Implications in sports injuries - Arroyo Moya, Wilson (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The objective was to analyze the evidence focused on the relationship of the ACTN3 R577X gene with flexibility and joint motion ranges and its influence on sports injuries. A systematic review of the literature was carried out applying the guidelines established in the PRISMA statement on the association of the ACTN3 gene with flexibility and joint range of motion. The search on PubMed, Scopus, SPORTDiscus and Google Scholar included original studies available in full text from January 2014. Deficiency of alpha-actinin-3 (Genotype XX) represented significantly greater flexibility and range of motion in most studies. In addition, it is associated with lower muscle stiffness. A relationship between ACTN R577X and muscle stiffness is evident, where the RR genotype would represent a greater risk of injury in sports that require high flexibility. The genetic component could be considered in injury prevention programs.